PENGARUH KOMPOSISI DAN TEKANAN PADA KOMPOSIT SERBUK GERGAJI KAYU DENGAN MATRIKS POLYPROPYLENE TERHADAP KEKUATAN TARIK, BENDING, DAN IMPACT - , TEUKU SADRI RAMADHAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final project raised about the effect of the composition of mass and pressure on wood sawdust composites with polypropylene matrix. Waste from wood sawdust results are generally discarded or not used by the people chosen as reinforcement in composites. This research aims to determine the effect of the mass composition and pressure during manufacture of the composite tensile strength, bending, and impact. Macro structure of the composite is also seen to determine the pattern of fiber composites. The mechanical properties of polypropylene matrix was also examined to determine differences in the strength of the composite after being given sawdust as an amplifier. The material used in this study is the type of wood sawdust sengon and clear plastic with polypropylene content ( PP ) as the matrix of the composite . The manufacture of composites begin with choosing a uniform sawdust approach by filtering, the size choosen was 1,19 mm . Variable mass composition of the composite , which is the ratio of wood sawdust : polypropylene is 50:50 ( K 55 ) and 60:40 ( K 64 ) . Composites prepared by layer on a mold with plastic PP at first , then wood sawdust , performed repeatedly until all 30 layers to get a more or less thick composite according to standard testing . Then the mold is heated using a thermocouple and in the press on a hydraulic press machine with different pressures as a variation , namely pressure 18 , 24 , and 29 kg / cm ² . The heating is done to a temperature of 190 º C for 15 minutes . Mold is cooled to about 60 º C in order to facilitate the release of the composite mold . Then to determine the mechanical properties of composites made several tests that test tensile , bending , and impact . Observation was also done using a microscope to see the macro structure of a composite , aims to look at the pattern of fibers plucked from the tensile test results of the composite. Based on the results of testing the mechanical properties, the strength of the composite K 64 bit stronger than the composite K 55. Tensile strength, bending, and fracture toughness of the composites increased at pressure 18 kg / cm ² to 24 kg / cm ² at each mass composition of the composite, but at a pressure of 29 kg / cm ² the strength of composites decreased. Macro structure of a composites explain about fiber pattern in form of a polypropyelene matrix bonding to wood sawdust, where the pressure of 29 kg / cm ² bonding to the fiber tends to decrease. Keywords: wood sawdust (sengon), polypropylene (PP), composites, mechanical properties, macro structur